Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1163/22941932-90000451
|View full text |Cite
|
Sign up to set email alerts
|

Sem Observations of Perforation Plates in Sonneratia Linn. (Sonneratiaceae)

Abstract: Vessels of Sonneratia belonging to the family Sonneratiaceae, have so far been shown to have only simple perforations. However, in the present study, simple, scalariform, modified scalariform and reticulate types of perforations in the vessels of four species of Sonneratia have been found for the first time. Besides scalarifonn and reticulate perforations, a variety of intermediate forms have also been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Composition of the fossil wood flora of Tsuyazaki. occasional scalariform and reticulate perforation plates are reported in modern Sonneratia (Rao et al 1987a, b), but we did not observe multiple perforation plates in the Kyushu fossil wood of Sonneratia.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Composition of the fossil wood flora of Tsuyazaki. occasional scalariform and reticulate perforation plates are reported in modern Sonneratia (Rao et al 1987a, b), but we did not observe multiple perforation plates in the Kyushu fossil wood of Sonneratia.…”
Section: Discussioncontrasting
confidence: 69%
“…The Kyushu fossil wood differs from the extant species in absence of crystals in ray cells, wider vessels (mean tangential diameter of those extant species is 88-95 μm whilst that of the fossil is 119 μm ) and shorter vessel elements (mean element length of the extant species is 650-670 μm whilst that of the fossil is 389 μm). Rao et al (1987a) reported the presence of a few (5-20%) scalariform, modified scalariform and reticulate perforation plates in addition to simple perforation plates in all four extant species. Only simple perforation plates have been observed in the Kyushu wood.…”
Section: Sonneratiaceaementioning
confidence: 97%